Finite element study of oxygen diffusion in the intervertebral disc - Sélard, E; Shirazi-Adl, A; Urban, J (2000)
The intervertebral disc consists of a water-rich extra-cellular matrix which is synthesized and maintained by its cells. The disc is the largest avascular tissue in the body with its cells lying as much as 8mm away from the blood supply. Nutrients, essential for maintaining cellular viability, diffuse through the matrix from blood supply under a concentration gradient arising from cellular demand. The oxygen concentration gradients in the intervertebral disc are investigated to examine the effects of exchange area and disc thickness on oxygen flux in the disc. The concentration gradients are computed using the two-dimensional Poisson's equation and measured values for oxygen consumption rate and oxygen diffusion.